The Impact of Probiotics Co-administration with Antibiotics on Health - Dey, Sreedeep; Sreejita Das (RADINKA JAYA UTAMA PUBLISHER, 2024)
Antibiotics have updated modern medicinal practices by improving outcomes in infectious diseases. The broad-spectrum action of antibiotics can cause disruption in the balance of beneficial gut bacteria that eventually leads to adverse effects such as antibiotic-associated diarrhea (AAD) and an increased susceptibility to sudden infections. When probiotics, or live microorganisms, are administered in proper amounts, they can benefit our health. Using probiotics is a potential solution to mitigate these adverse effects. This review aims to provide a comprehensive analysis of the impact of probiotics co-administered with antibiotics on various aspects of health, including the prevention of AAD, modulation of gut microbiota, and enhancement of immune function. This research uses a literature review method, namely a series of activities related to collection methods of library data. the co-administration of probiotics with antibiotics represents a promising approach to mitigating the adverse effects of antibiotic therapy on gut health and overall well-being. Additionally, the potential mechanisms underlying these effects and highlighting the challenges and future directions in this field have also been discussed.